An Efficient Synthesis of 1-chloro-2, 2-difluoroethylene via the Reductive Dechlorination of 1, 2, 2-trichloro-1, 1-difluoroethane. (May 2013) - Wang, Nong; Yang, Lijuan; Xiang, Shaoji
1-Chloro-2, 2-difluoroethylene was prepared from 1, 2, 2-trichloro-1, 1-difluoroethane by reductive dechlorination in the presence of zero-valent zinc. Eleven different solvents were investigated and the best results were obtained in methanol, dimethyl formamide and ethanol at 80 °C. A large-scale experiment using ethanol as a solvent gave 1-chloro-2, 2-difluoroethylene in high yield. These results provide a method for producing 1-chloro-2, 2-difluoroethylen e on an industrial scale because 1, 2, 2-trichloro-1, 1-difluoroethane is the waste material arising from 2, 2-dichloro-1, 1, 1-trifluoroethane production. These results can also provide a method for solving the recycling problem of 1, 2, 2-trichloro-1, 1-difluoroethane in 2, 2-dichloro-1, 1, 1-trifluoroethane production.